Analyze The Influence of Current Ratio, Debt to Equity Ratio, Earning Per Share, Return on Asset on Stock Return at Coal Mining Company Listed on Indonesia Stock Exchange Period 2013-2016 - Sinaga, Isma Khairani; Astini, Rina (International Humanities and Applied Science Journal, 2021)
This research conducted to analyze and to know the influence of Current Asset (CR), Debt to Equity Ratio (DER), Earning Per Share(EPS) and Return On Asset (ROA) on Stock Return at coal mining company listed on Indonesia Stock Exchange period 2013-2016. The population used in this research is all coal mining companies listed in Indonesia Stock Exchange 2013-2016. The sample of this research are 17 coal mining companies that appropriate the criteria. The analysis technique used in this research is panel data regression with using Eviews 9. Based on Chow test and Hausman test Panel Data Regression Model selected Is Fixed Effect Model. Based on t-test the result showed that Current Ratio (CR) has a significant effect on Stock Return, Debt to Equity Ratio (DER) has no significant effect on Stock Return, Earning Per Share(EPS) has no significant effect on Stock Return, and Return On Assets (ROA) has no significant effect on Stock Return. Based on F-test the result show that Current Ratio, Debt to Equity Ratio, Earning Per Shareand Return On Asset has a significant effect on Stock Return.Keywords : Stock Return, CR, DER, EPS, ROA